ASSESSMENT OF RAINFALL FORECAST ACCURACY FOR VIZIANAGARAM DISTRICT OF NORTH COASTAL ANDHRA PRADESH - A, ALIVENI (The Journal of Research ANGRAU, 2026)
The rainfall forecast and validation are important because of the socio-economic implicationsfor the nation. An attempt was made to confirm the correctness and dependability of the spatialrainfall forecast of Vizianagaram district of North Coastal Andhra Pradesh during the year 2024 2025.The rainfall forecast provided by IMD, Pune for Vizianagaram districtwas verified with dailyobserved weather data obtained from the Chief Planning Office,by calculating a variety ofcategorical statistical measures from the elements of the contingency table on seasonal basis.Statistics were presented for Percentage correct (PC),Probability of Detection(POD), CriticalSuccess Index (CSI), Heidke Skill Score (HSS) and Hansen Kuipers score(HKS) of the districtwise forecast.Overall, rainfall accuracy was found to be successful, with moderate to highperformance. The positive HSS and HKS indicated the reliability of forecast at satisfactory level.